Translating gene therapy to the clinic techniques and approaches - Laurence, Jeffrey; Franklin, Michael 1972- (Advances in translational research, 2015)
Translating Gene Therapy to the Clinic, edited by Dr. Jeffrey Laurence and Michael Franklin, follows the recent, much-lauded special issue of Translational Research in emphasizing clinical milestones and critical barriers to further progress in the clinic. This comprehensive text provides a background for understanding the techniques involved in human gene therapy trials, and expands upon the disease-specific situations in which these new approaches currently have the greatest therapeutic application or potential, and those areas most in need of future research. It emphasizes methods, tools, and experimental approaches used by leaders in the field of translational gene therapy. The book promotes cross-disciplinary communication between the sub-specialties of medicine, and remains unified in theme